Son Dönem Osmanlı düşüncesinde irade hürriyeti (1908-1918) - Özdinç, Rıdvan (My University, 2010)
Bu çalışmamız Son Dönem Osmanlı ulema ve mütefekkirlerinin irade meselesi etrafındaki görüşlerini ele almaktadır. Devir olarak II. Meşrutiyet’le sınırlı tutulan bir zaman diliminde Kelam ilminin önemli konularından biri olan irade meselesinin modernleşmeyle beraber değişimi ve dönüşümü ele alınmaktadır. Tanzimat sonrasında Avrupa’yla gelişen münasebetler, bizzat oryantalistlerin İslam dünyasına ve Müslümanlığa yönelik iddia ve suçlamaları, Tanzimat’la birlikte siyasi yapıda meydana gelen değişiklikler yeni bir toplum yapısı ve insan tipi arayışına hız vermiştir. Yeni bir insan tipi arayışına girişen Osmanlı ulema ve aydınlarının bu çerçevede irade meselesini ele alışları incelenmiştir. İtikâdî Mezheplerin bu arayışlardaki rolleri ve irade meselesi altında incelenen konuların modernleşmeyle irtibatları tezin ana mihverini teşkil etmektedir. Yeni İlm-i Kelam dönemi olarak da isimlendirilen bu dönemde hürriyet kavramıyla da ilgili olarak irade, kaza ve kader meseleleri ve bunların tariflerinde yapılan değişiklikler din ve modernleşme ilişkileri zaviyesinden ehemmiyetlidir. İrade meselesinin içtimâî-ahlâkî-siyasî tezahürleri, Allah-insan ilişkilerini ifade eden kavramların seyri üzerinden incelenmiş ve kelâm-ahlâk ilişkisinin tezahürü olan bu konuların şahsî ve içtimâî izleri sürülmüştür. Bütün bu tartışma ve arayışların tarihî mirasla benzeşen ve farklılaşan yönlerine işaret edilmiştir.

The Freedom of Will in The Last Period of Ottoman Thought (1908- 1918) This study deals the ideas of scholars and thinkers of the last Ottoman period on the problem of irada (will), which is one of the most important subject in Islamic theology. The change and transformation of the concept of will with the Ottoman modernisation is handled in the work. The relations developed with Europe after Tanzimat, some accusing arguments directed by some orientalists to Muslim world and the changes in political structure due to Tanzimat had accelerated search for a new social structure and human type. In this scope, our thesis focuses on the approaches of Ottoman scholars and intellectuals with the problem of will in this period. The status of theological sects as well as their roles in the above-mentioned search endeavor and the relations of the subjects with modernisation, which are examened under the problem of will, are the main themes of this thesis. The problems of irada (will) and qadar (predestination) and the changes occured in their definitons in this period, which is also called “Yeni İlm-i Kelâm” period, are highly important from the aspect of relationship between religion and modernisation. The social, ethical and political reflections of the problem of will are analysed through the journey of concepts that express god-human relations. Additionally, personal and social sides of these topics that are at the same time the appearance of theology-ethic relation are examined. It is also indicated that the aspects of all these discussions and pursuits even differ from or resemble to the historical heritage.
Keywords: İslam Dini; Kelam